GERMAN PATTERN MELODIES OF THE 16ᵀᴴ CENTURY PROTESTANT HUNGARIAN HYMNS - Ágnes TÖRÖK (Studia Universitatis Babeş-Bolyai. Musica)
The appearance of the hymns of the German Protestantism in Hungary were clear and reasonable from theological and practical points of view of as well. This essay discusses the hymns and does not draw a distinction between the text writer Luther and the melody writer Luther or other German hymn writer priests. On the basis of István Gálszécsi’s and Gallus Huszár’s Hymnal this essay proves that the majority of the foreign melodies of the sixteenth century Hungarian Protestant song-material shows German relations despite some of today’s conclusions. When comparing vernacular songs we can draw up conclusions about their origins only through clear-cut differences. By identifying the possible German sources the proportion of the German and Hungarian chants can be defined well.